Global Biodiversity : Volume 2: Selected Countries in Europe - Pullaiah, T.; Apple Academic Press (Toronto ; New Jersey : Apple Academic Press, 2018)
This is the second volume in the new multi-volume set, Global Biodiversity.Each volume in this series covers the biodiversity of a selection of nations in particular regions of the world. The volumes discuss and summarize the available information on both wild and cultivated plants, wild and domesticated animals, and the variety of microbes of the different nations. Global Biodiversity, Volume 2: Selected Countries in Europe looks at the biodiversity of selected countries of Europe, providing an abundance of biodiversity information on Bosnia-Herzegovina, France, George, Greece, Hungary, Italy, Norway, Serbia, Slovakia, Sweden, Turkey, and the United Kingdom. Each chapter features a different country and is written by research scientists and conservationists. The information covers geographical status, ecosystem diversity, species diversity, genetic diversity, and conservation efforts in that particular country. The authors provide statistical data on plants, animals, and microbes of that country along with genetic diversity with the focus on crop plants/cultivated plants and domesticated animals and their wild relatives.
Biodiversity of Bosnia-Herzegovina -- Senka Barudanovic -- Biodiversity in France -- Philippe Grandcolas -- Biodiversity of Georgia -- GuramAleksidze et al. -- Biodiversity of Greece -- Anastasios Legakis, Theophanis Constantinidis, and Panos V. Petrakis -- Biodiversity in Hungary -- Zoltn Varga -- Biodiversity in Italy -- Gianniantonio Domina and Marzio Zapparoli -- Biodiversity in Norway -- Kjetil Bevanger -- Biodiversity in Serbia -- Biljana Panjkovi and Slobodan Puzovi -- Biodiversity of Slovakia -- Libor Uirych et al. -- Biodiversity of Sweden -- Ulf Grdenfors -- Biodiversity in Turkey -- Ali A. Dnmez and Sedat V. Yerli -- Biodiversity in the United Kingdom Ranee -- Om Prakash and Fred Rumsey.
Includes bibliographical references and index.
Also available in print format.
Keywords: Biodiversity -- Europe; Biodiversity; Electronic books